Performing "in the red": transformations and tensions in repertoires of contention during the 2012 Quebec student strike. (2nd September 2016) - Spiegel, Jennifer Beth
Abstract: The longest and largest student strike in Canadian history began in Quebec in the spring of 2012 in resistance to proposed tuition hikes and the increasing privatization of education and public services that this signaled. The symbol of the student movement, the red square (denoting 'squarely in the red' or 'squarely in debt') quickly went 'viral'. At its height, an estimated 300, 000 students were striking – nearly 75% of Quebec's post-secondary student population; on May 22nd some 500, 000 people marched in support. The strike continued for six months, ending only after the government was overturned and a new government cancelled the tuition increase. The redeployment of local protest repertoires, including traditional tactics such as picket lines combined with inclusive and creative tactics popularized in alter-globalization movements. Formal student associations combined with various ad hoc coalitions and organizations, as well as communitarian groups, in an uneasy alliance to create a mass mobilization that some commentators dubbed Québec's 'Maple Spring'. This article documents the transformation of what Tilly has called 'repertoires of contention' within the context of the Quebec student movement. In so doing, it highlights some of the principle debates concerning social values and distributions of agency that resurfaced in connection with the diverse tactics that formed the 'new' combinational repertoire.